Analisis Life Cycle Assessment (LCA) terhadap berbagai jenis kemasan produk perikanan di Kabupaten Pangkep - Musdalifah Musdalifah; Yakub Yakub; Rasdi Rasdi (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the environmental impact and effectiveness of various types of fishery product packaging in Pangkajene and Kepulauan (Pangkep) Regency, South Sulawesi, and assess the perceptions of industry players and consumers. Data were obtained from 15 SMEs, 5 distributors, and 30 consumers through surveys, interviews, and laboratory tests. The results show that 80% of SMEs still use conventional plastic (PP/PE), 3 large exporters use multilayer packaging, and 2 SMEs are trying biodegradable alternatives. Life Cycle Assessment (LCA) analysis shows that multilayer has the highest environmental impact with a carbon footprint of 4.5 kg CO₂ eq per kg of product, conventional plastic 3.2 kg CO₂ eq, while biodegradable has the lowest at 1.4 kg CO₂ eq. Effectiveness tests show that multilayer is the most protective with a shelf life of up to 12 months, conventional plastic only 2-3 months with the risk of additive migration, while biodegradable can maintain quality for 3-6 months but is less resistant to moisture. The survey revealed that 70% of consumers are willing to pay more for environmentally friendly products, while 60% of industries struggle to switch due to high costs, although 90% support government incentives. The study concluded that biodegradable packaging has the potential to become a sustainable packaging solution with policy support and research and development based on locally sourced materials.